How Do Different Reanalysis Radiation Datasets Perform in West Qilian Mountains? - Yingshan, Wang; Weijun, Sun; Lei, Wang; Yanzhao, Li; Wentao, Du; Jizu, Chen; Xiang, Qin (Frontiers in Earth Science, 2022)
Solar radiation plays an important role in the cryospheric water cycle, especially in alpine regions. This study presents an evaluation of the MERRA2, ERA5, HAR v2, JRA-55 and NCEP/CFSR reanalysis datasets at different time scales by comparing observed datasets from July 2010 to December 2015 at 4550 m in the Laohugou Basin. In terms of shortwave radiation, ERA5 performs significantly better than the other reanalysis radiation datasets. For downward shortwave radiation, HAR v2 performs better than ERA5 on only two timescales, 3 months and half-year, with MAEs of 13.28w/m2 and 7.96 w/m2. The upward shortwave radiation, ERA5, outperforms the other reanalysis datasets on all 12 timescales. For downward longwave radiation, ERA5 also performs significantly better, with only MERRA2 outperforming ERA5 on the daily scale and annual scale, with R2, bias, RMSE, and MAE of 0.6, 0.95; -9.51 w/m2, -9.41 w/m2; 34.98 w/m2, 9.46 w/m2; and 27.52 w/m2, 9.41 w/m2, respectively. In the upward longwave radiation, HAR v2 performs better than the other reanalysis datasets on all timescales, except for ERA5, which has a better R2 of 0.92 on the annual scale. All the reanalysis datasets can show the variation trend of the four radiation parameters in different seasons and achieve a better performance in winter. Therefore, ERA5 is recommended for regions without shortwave radiation observations, and HAR v2 and ERA5 are recommended for longwave radiation simulations. Although there are obvious shortcomings in the reanalysis radiation datasets, they still provide important supplementary information for research in high-altitude areas, where the observed datasets are too sparse.